Using UML to model presentational of web application. - Ahmad Sharif, Mohd. Nazir; Ahmad, R. Azmi; Syed Abd. Rahman, Syed Mohd. Haidzir; Zakaria, Nor Hidayati (Penerbit UTM Press, 2002)
Web-based applications are currently become more complex system. The range of Web-based applications varies enormously, from simple static Web sites that are essentially hypertext document presentation applications, to sophisticated high-volume e-comtnerce applications often involving supply, sourcing, ordering, payment tracking and dispatch of goods or the provision of services. In other words, it provides users with business logic facilities, navigational structure, and also presentational aspects. In the context of presentational design, Web applications often contain significant multimedia content such as images, movie clips, sound clips and text, requiring specialist mechanism for their development. These elements of presentational need for mechanisms that can be used to support the modeling of user interfaces, which showing how navigational is presented to the user. We choose UML as modeling tool for presentational design, based on two important advantages. First, UML has been become a de facto standard for the design of object oriented systems. Second, and the most important one. CASE tools supporting UML can be used in the Web application development process. Note, UML can be used to model different kinds of systems such as software systems, hardware systems, and real-world organizations. The purpose of this paper is to show how UML notation and UML modeling techniques can be used in the Web application presentational modeling. UML stereotypes are specified for presentational design, according to the UML extension mechanisms defined in UML.